Usability of the bivalves Dreissena polymorpha and Anodonta anatina for a biosurvey of the neurotoxin BMAA in freshwater ecosystems. (April 2020) - Lepoutre, A.; Hervieux, J.; Faassen, E.J.; Zweers, A.J.; Lurling, M.; Geffard, A.; Lance, E.
Abstract: The environmental neurotoxin β-methylamino-L-alanine (BMAA) may represent a risk for human health in case of chronic exposure or after short-term exposure during embryo development. BMAA accumulates in freshwater and marine organisms consumed by humans. It is produced by marine and freshwater phytoplankton species, but the range of producers remains unknown. Therefore, analysing the phytoplankton composition is not sufficient to inform about the risk of freshwater contamination by BMAA. Filter-feeders mussels have accumulation capacities and therefore appear to be relevant to monitor various pollutants in aquatic ecosystems. We investigated the suitability of the freshwater mussels Dreissena polymorpha and Anodonta anatina for monitoring BMAA in water. Both species were exposed to 1, 10, and 50 μg of dissolved BMAA/L daily for 21 days, followed by 42 days of depuration in clean water. On days 0, 1, 7, 14, and 21 of exposure and 1, 7, 14, 21 and 42 of depuration, whole D. polymorpha and digestive glands of A. anatina were sampled, and the total BMAA concentration was measured. D. polymorpha accumulated BMAA earlier (from day 1 at all concentrations) and at higher tissue concentrations than A. anatina, which accumulated BMAA from day 14 when exposed to 10 μg BMAA/L and from day 7 when exposed to 50 μg BMAA/L. As BMAA accumulation by D. polymorpha was time and concentration-dependent, with a significant elimination during the depuration period, this species may be able to reflect the levels and dynamics of water contamination by dissolved BMAA. The species A. anatina could be used for monitoring water concentrations above 10 μg BMAA/L. Graphical abstract: Image 1 Highlights: D. polymorpha and A. anatina could be used to biomonitor BMAA. Whole D. polymorpha could reveal BMAA levels/dynamics from 10 μg dissolved BMAA/L. Digestive glands of A. anatina could reveal BMAA level from 50 μg dissolved BMAA/L. Active monitoring should be preferred to a passive one. Abstract : D. polymorpha and A. anatina could be used to biomonitor BMAA in fresh water.